2014
DOI: 10.3171/2014.7.focus14203
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic supraorbital eyebrow approach for the surgical treatment of extraaxialand intraaxial tumors

Abstract: Object The supraorbital eyebrow approach is a minimally invasive technique that offers wide access to the anterior skull base region and parasellar area through asubfrontal corridor. The use of neuroendoscopy allows one to extend the approach further to the pituitary fossa, the anterior third ventricle, the interpeduncular cistern, the anterior and medial temporal lobe, and the middle fossa. The supraorbital approach involves a limited skin incision, with minimal sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 25 publications
(33 reference statements)
0
35
0
3
Order By: Relevance
“…A large sinus increases the risk of postoperative CSF leakage and alters the surgical trajectory. 17 Combining the supraorbital approach with the endonasal approach when necessary reduced the number of CSF leaks to 0 in our series. The basic concept here is to recognize the limits and limitations of each approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large sinus increases the risk of postoperative CSF leakage and alters the surgical trajectory. 17 Combining the supraorbital approach with the endonasal approach when necessary reduced the number of CSF leaks to 0 in our series. The basic concept here is to recognize the limits and limitations of each approach.…”
Section: Discussionmentioning
confidence: 99%
“…17 A recent literature review has demonstrated that a total of 81 cases of olfactory groove meningiomas removed using the supraorbital eyebrow approach have been reported. 44 Of these, GTR was achieved in 91.4%.…”
Section: Discussionmentioning
confidence: 99%
“…В хирургии внутримозговых объемных образова-ний, как глиом, так и метастазов, очень важен детальный предоперационный анализ данных МРТ [7]. В первую очередь важно оценивать, какой тип резекции плани-руется.…”
Section: Discussionunclassified
“…-тотальная: при отсутствии контрастного усиле-ния для опухолей, накапливающих контраст; -почти тотальная: при удалении более 90 % опухоли; -субтотальная: при удалении менее 90 % опухо-ли [7,14].…”
Section: Introductionunclassified
“…1 The keyhole supraorbital approach has steadily become a workhorse operation for neurosurgeons who routinely treat tumors and aneurysms in these anatomical regions. 2 The authors are to be acknowledged for further developing this minimally invasive approach and for routinely integrating the endoscope into their practice, which improves overall visualization and facilitates inspection around anatomical corners such as the tuberculum sellae.…”
mentioning
confidence: 99%